2005
DOI: 10.1099/jmm.0.45861-0
|View full text |Cite
|
Sign up to set email alerts
|

Depletion of lymphocytes, but not neutrophils, via apoptosis in a murine model of Vibrio vulnificus infection

Abstract: Vibrio vulnificus causes severe sepsis in humans. There are several reports about the relationship between host immunity and bacterial growth in V. vulnificus infection. However, the effect on leukocytes of V. vulnificus infection in vivo has not been elucidated. A murine model of V. vulnificus infection was used to investigate its effects on leukocytes in this study. Bacteria were recovered from the blood of mice 3 h after subcutaneous injection in the right lower flank. They were detected in 87 . 5 % (n ¼ 7/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 24 publications
0
17
0
Order By: Relevance
“…Blood taken from patients with chronic liver disease showed decreased neutrophil activity compared to the blood of healthy individuals, and survival of V. vulnificus in human blood is inversely correlated with phagocytosis by neutrophils (44). Based on these data and a study showing increased neutrophil concentrations in the peritoneal cavity upon infection with V. vulnificus, the response of neutrophils to V. vulnificus has been implicated as a disease determinant for this organism (44,56,144,154). One of these studies, however, did use unencapsulated strains (the significance of which is discussed later in this review), thus diminishing the potential role neutrophils play in controlling V. vulnificus infection (44,154).…”
Section: Host Resistancementioning
confidence: 99%
See 2 more Smart Citations
“…Blood taken from patients with chronic liver disease showed decreased neutrophil activity compared to the blood of healthy individuals, and survival of V. vulnificus in human blood is inversely correlated with phagocytosis by neutrophils (44). Based on these data and a study showing increased neutrophil concentrations in the peritoneal cavity upon infection with V. vulnificus, the response of neutrophils to V. vulnificus has been implicated as a disease determinant for this organism (44,56,144,154). One of these studies, however, did use unencapsulated strains (the significance of which is discussed later in this review), thus diminishing the potential role neutrophils play in controlling V. vulnificus infection (44,154).…”
Section: Host Resistancementioning
confidence: 99%
“…In addition to neutrophils, macrophages have also been suggested to play a part in defense against V. vulnificus. During infection, this bacterium reduces the number of lymphocytes through apoptotic activity, but neutrophil numbers do not decrease, indicating that other leukocytes are being targeted (56). Specific examination of macrophages revealed that clinical strains of V. vulnificus were able to induce macrophage apoptosis (57).…”
Section: Host Resistancementioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Kashimoto et al reported that lymphocytes but not neutrophils were depleted, via apoptosis, by V. vulnificus (12). Extensive loss of lymphocytes was observed in patients due to polymicrobial sepsis, and in a mouse model of sepsis, polycaspase and caspase 3 inhibitor prevented lymphocyte apoptosis and improved survival (9,10).…”
mentioning
confidence: 99%
“…Isolated peripheral lymphocytes (1.0  10 6 cells/ml) suspended in RPMI-1640 medium were incubated with Dex or organotin compounds at 37C for 1 or 3 hr. After incubation, the lymphocytes were stained with FITCAnnexin V and propidium iodide (PI) using an Annexin-V-FLUOS Staining Kit (Roche Diagnostics GmbH, Penzberg, Analysis of DNA fragmentation: DNA fragmentation was analyzed as described previously with some modifications [14,27]. Briefly, thymus tissues from the mice were gently glass-ground to dissociate the cells, suspended in cold HBSS and then gently passed through a stainless steel mesh to obtain single-cell suspensions of thymocytes.…”
Section: Chemicalsmentioning
confidence: 99%